DEVELOPING HIGH-PERFORMANCE GeTe AND SnTe-BASED THERMOELECTRIC MATERIALS - Yang, Zan (My University, 2022)
This dissertation covers the study of the thermoelectric properties of GeTe and SnTe. The goal of this research is to develop high-performance lead-free thermoelectric materials that can replace PbTe-based systems so that thermoelectric technology could be bring into real application. During the study, extensive investigations on the electrical and thermal transport behaviors were conducted both experimentally and theoretically. In Chapter 1 ~ 3, the origin of thermoelectricity, modelling and characterization methods are discussed in detail. In Chapter 4, study on the thermoelectric properties of Bi, Zn and In co-doped GeTe was presented. Initial doping with Bi enhanced the performance by tuning the electronic properties and bringing down the thermal conductivity. Subsequent Zn doping permitted to maintain the high power factor by increasing carrier mobility and reducing carrier concentration. Subsequent In doping boosted the density of state effective mass. A peak zT value of 2.06 and an average zT value of 1.30 have been achieved in (Ge0.97Zn0.02In0.01Te)0.97(Bi2Te3)0.03. In Chapter 5, we thoroughly investigated the transport properties of SnTe-Sb2Te3 alloying system, provided useful insight of the mechanism of the enhanced Seebeck coefficient. To also overcome the poor carrier mobility, Pb compensation was performed which effectively optimized the carrier mobility. Meanwhile, Pb compensation broke the charge balance, allowing Sb to precipitate out of the structure. These second-phase particles provided additional source of phonon scattering, effectively suppressing the lattice thermal conductivity. As a result, a peak zT of 1.1 at 778K and an average zT of 0.56 from 300K to 778K was achieved in (Sn0.98Ge0.05Te)0.91 (Sb2Pb0.5Te)0.09, which is one of the best SnTe-based thermoelectric systems.
Keywords: Thermoelectric; Density functional theory; Band Engineering; Defect Engineering